Enhanced photocatalytic activity of micro/nano textured TiO2 surfaces prepared by sandblasting/acid-etching/anodizing process - DEMİRCİ, SELİM (ELSEVIER SCIENCE SA, 2017)
In this study, micro-textured titanium surfaces were created by sandblasting and acid-etching methods. Nanostructured titanium dioxide (TiO2) films were synthesized on the micro-textured titanium surfaces by anodizing method. Subsequently, anodized (A), acid-etched/anodized (EA), sandblasted/anodized (SA) and sandblasted/acid-etched/anodized (SEA) samples were fabricated. Structural and morphological properties of the prepared samples were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM) and atomic force microscopy (AFM). Furthermore, surface roughness and wettability of the samples were evaluated by means of profilometry and contact angle measurement systems, respectively. Finally, the photocatalytic activities of the samples were determined by using aqueous methylene blue (MB) solutions under a specific UV light illumination for different periods of time. The obtained results pointed out that sandblasting and acid-etching treatment improved the surface roughness of the samples significantly. The photocatalytic experimental results showed that micro textured surface accelerated the degradation of MB, if compared to samples which are anodized without any of the regarding surface treatments. To sum up, sandblasted/acid-etched/anodized titanium surfaces exhibited the highest wettability, surface roughness and photocatalytic activity among the samples. The present study may shed new light on the modification of titanium surfaces. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Nanostructured TiO2 films; Sandblasted/acid-etched titanium; Photocatalytic degradation; Surface morphology; Texture; PHOTOELECTROCHEMICAL PROPERTIES; CALCINATION TEMPERATURE; THIN-FILMS; TITANIUM; ANATASE; OXIDE; WETTABILITY; ANODIZATION; FABRICATION; MORPHOLOGY